Lactate minimum underestimates the maximal lactate steady-state in swimming mice - Rodrigues, Natália de Almeida, 1986- (2017)
Abstract: The intensity of lactate minimum (LM) has presented a good estimate of the intensity of maximal lactate steady-state (MLSS); however, this relationship has not yet been verified in the mouse model. We proposed validating the LM protocol for swimming mice by investigating the relationship among intensities of LM and MLSS as well as differences between sexes, in terms of aerobic capacity. Nineteen mice (male: 10, female: 9) were submitted to the evaluation protocols for LM and MLSS. The LM protocol consisted of hyperlactatemia induction (30 s exercise (13% body mass (bm)), 30 s resting pause and exhaustive exercise (13% bm), 9 min resting pause and incremental test). The LM underestimated MLSS (mice: 17.6%; male: 13.5%; female: 21.6%). Pearson’s analysis showed a strong correlation among intensities of MLSS and LM (male (r = 0.67, p = 0.033); female (r = 0.86, p = 0.003)), but without agreement between protocols. The Bland-Altman analysis showed that bias was higher for females (1.5 (0.98) % bm; mean (MLSS and LM): 4.4%–6.4% bm) as compared with males (0.84 (1.24) % bm; mean (MLSS and LM): 4.5%–7.5% bm). The error associated with the estimated of intensity for males was lower when compared with the range of means for MLSS and LM. Therefore, the LM test could be used to determine individual aerobic intensity for males (considering the bias) but not females. Furthermore, the females supported higher intensities than the males. The differences in body mass between sexes could not explain the higher intensities supported by the females